Does acute kidney injury affect survival in adults with acute respiratory distress syndrome requiring extracorporeal membrane oxygenation?. (July 2018) - Devasagayaraj, Richard; Cavarocchi, Nicholas C.; Hirose, Hitoshi
Introduction: Patients who develop severe acute respiratory distress syndrome (ARDS) despite full medical management may require veno-venous extracorporeal membrane oxygenation (VV ECMO) to support respiratory function. Survival outcomes remain unclear in those who develop acute kidney injury (AKI) requiring continuous renal replacement therapy (CRRT) during VV ECMO for isolated severe respiratory failure in adult populations. Methods: A retrospective chart review (2010-2016) of patients who underwent VV ECMO for ARDS was conducted with university institutional review board (IRB) approval. Patients supported by veno-arterial ECMO were excluded. AKI was defined by acute renal failure receiving CRRT and the outcomes of patients on VV ECMO were compared between the AKI and non-AKI groups. Results: We identified 54 ARDS patients supported by VV ECMO (mean ECMO days 12 ± 6.7) with 16 (30%) in the AKI group and 38 (70%) in the non-AKI group. No patient had previous renal failure and the serum creatinine was not significantly different between the two groups at the time of ECMO initiation. The AKI group showed a greater incidence of complications during ECMO, including liver failure (38% vs. 5%, p=0.002) and hemorrhage (94% vs. 45%, p=0.0008). ECMO survival of the AKI group (56% [9/16]) was inferior to the non-AKI group (87% [33/38], p=0.014). Conclusions: Our study demonstrated that VV ECMO successfully manages patients with severe isolated lung injury. However, once patients develop AKI during VV ECMO, they are likely to further develop multi-organ dysfunction, including hepatic and hematological complications, leading to inferior survival.